Pay Inequity: A Comparative Analysis of Pay Inequality in the United States by Selected Correlates - Roger Klomegah; Nikelle Fleming (Journal of Public and Professional Sociology)
This study examined the socio-demographic associates of income inequality within the context of human capital and wage discrimination theories. General Social Survey (GSS) data set (2010), comprising a sample size of 2044 respondents were utilized in analysis. Income categories (low and high) were regressed on predictive variables: gender, racial categories (White, Black, and Other), education, type of occupation, U.S. citizenship status, age, and work experience. The results show that gender, education, U.S. citizenship status, age, and work experience were significant predictors of the likelihood of a respondent belonging to a low or high income group. It is suggested that future research should consider demographic factors such as immigration status, place of origin, and age that have been less examined in wage inequality research. In addition, the merit of discrimination theory needs to be verified more instead of human capital theory which has been extensively tested.